Automated RFID-based home lock and monitoring system / Muhammad Afiq Irfan Baharuddin - Baharuddin, Muhammad Afiq Irfan (2024)
Automated RFID-based Home Lock and Monitoring System is a system that is focusing on enhanced security in daily environment, particularly in residential setting, by proposing and implementing an RFID door lock system using Arduino technology. The aim is to improve the shortcomings of traditional lock systems such as vulnerability to missing by introducing a more secure and efficient method of access control. The RFID door lock system seeks to offer faster access while ensuring greater safety by utilizing RFID technology to verify and grant access only to individuals possessing the correct RFID tags. The overall goal is to create a robust security system for restricted areas that is both reliable and trackable using Arduino as the microcontroller. This whole system is designed for the residents who had a lot of burglar cases in their environment. Residents' safety is promised by this little and creative hardware ensemble